General Performance, Combining Abilities and Heritability of Yield and Yield Component Traits in Pumpkin (Cucurbita moschata Poir.) at Different Conditions - Elhameid Abdein*, Mohamed Abd; Fathi Hassan, Horeya Mohamed; Mohamed Dalia, Hikal (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Complete diallel cross 4 × 4 of pumpkin with their parents was evaluated for the genetic behavior of yield and yield component traits at two locations in Egypt. Four different pumpkin varieties belong to the species (Cucurbita moschata Poir.) were selected to use in this study. The parents Bugle Pumpkin and Long Island Cheese Pumpkin gave good combinations with the other parental lines to produce the highest F1 hybrid and the two hybrids (Bugle Pumpkin × Long Island Cheese Pumpkin) and (Long Island Cheese Pumpkin × Bugle Pumpkin) appeared the highest values in most studied traits. The present investigation included the estimation of general combining ability, specific combining ability, genetic parameters and heritability in both broad and narrow senses. The estimation of genetic parameters showed that the additive genetic variance was very important for the most studied traits. The results showed that both additive and non-additive genetic gene were positive for all studied yield and yield component traits except additive genetic variance for fruit diameter (F.D.cm), weight of fruit (W.F. g), flesh thickness (F.T.cm)and seeds weight (S.W.gm). In addition, the estimates of heritability in broad sense were larger in magnitudes than their corresponding values in narrow sense. Heritability in broad sense ranged from 99.224 to 99.762% for fruit length (F.L.cm) and fruit diameter (F.D.cm) for the combined data. In the same time, the highest value of h2n% were 57.196% for the combined data for fruit shape index (F.Sh.I.) trait. Keywords: combining abilities, diallel, genetic parameters, heritability, pumpkin *Corresponding author: Tel. 00201091448116 E-mail: abdeingene@yahoo.com